Una Casa de Moneda provincial bajo administración privada: Arequipa, 1837-1842 - Luque, Juvenal (2006)
The following one articulates it is a rehearsal that tries to present the problem that surrounded the operation of the House of Currency in their first stage, when it was low the private administration. The knowledge on the history of this republican mint is very scanty and that that here is sought it is to enlarge this panorama with you move news like the inventory of the machineries, a documental annex, the global montos of monetization and it is demonstrated that the coinage didn’t enter to the local commercial circuits if it didn’t leave to the exterior via export, reinforced this tendency with the fact that the mint only coins the calls currencies of high value (pesos and means pesos).